2023
DOI: 10.1002/rse2.326
|View full text |Cite
|
Sign up to set email alerts
|

Colony‐nesting gulls restrict activity levels of a native top carnivore during the breeding season

Abstract: Although nesting in colonies can offer substantial reproductive benefits for many seabird species, increased visibility to predators remains a significant disadvantage for most colony‐breeders. To counteract this, some seabird species have evolved aggressive nest defense strategies to protect vulnerable eggs and chicks. Here, we used an experimental approach to test whether colony inhabitance by breeding gulls Larus spp. in western Norway impacts visitation rates of a native, mammalian predator, the Eurasian o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 58 publications
(85 reference statements)
1
2
0
Order By: Relevance
“…Although the probability of attack was randomly distributed withing the colony, the frequency of attacks was strongly correlated with the abundance of the seagull’s chicks. Similar mobbing behaviours have been recorded in other seabirds’ colonies (Clode et al, 2000; Larsen, 1991), and in some cases it has been reported that other species use this indirect protection on their advantage (Gameiro et al, 2022; Guidos et al, 2023). For example, Monk parakeets ( Myiopsitta monachus ), an IAS built their nest under those of white storks ( Ciconia ciconia ) to reduce predation risk which indirectly offers protection against predators (Hernández-Brito et al, 2020).…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…Although the probability of attack was randomly distributed withing the colony, the frequency of attacks was strongly correlated with the abundance of the seagull’s chicks. Similar mobbing behaviours have been recorded in other seabirds’ colonies (Clode et al, 2000; Larsen, 1991), and in some cases it has been reported that other species use this indirect protection on their advantage (Gameiro et al, 2022; Guidos et al, 2023). For example, Monk parakeets ( Myiopsitta monachus ), an IAS built their nest under those of white storks ( Ciconia ciconia ) to reduce predation risk which indirectly offers protection against predators (Hernández-Brito et al, 2020).…”
Section: Discussionsupporting
confidence: 81%
“…These same ravines and platforms are used by L. michahellis colony for breeding and resting. The yellow-legged gull, as many other bird species, present an aggressive anti-predator behaviour specially during the breeding season (Clode et al, 2000; Frixione & Salvadeo, 2021; Gameiro et al, 2022; Guidos et al, 2023). Previous studies showed how seabird breeding colonies, due to its aggressive response to predators, work as facilitators for breeding of less aggressive and/or solitary species (Erwin, 1988; Gameiro et al, 2022; Quinn & Ueta, 2008; D. S. Richardson & Bolen, 1999).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation